ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BURNOUT SYNDROME PADA PEKERJA PT PLN (PERSERO) KANTOR PUSAT TAHUN 2022 - Veronica Christie Guesteva (2023)
Burnout syndrome is syndrome of prolonged physical, mental and emotional exhaustion from work. The PLN Head Office is the center of PLN's business in Indonesia, where employees carry significant responsibilities increasing the risk of burnout. This study analyzes the factors associated with burnout syndrome in PT PLN (Persero) Head Office employees in 2022. This research is quantitative cross-sectional design study with population all employees of General Division and HSSE Division of PT PLN (Persero) Head Office. The independent variables used were age, gender, marital status, years of service, work motivation, and social support with the dependent variable was burnout syndrome. Determined the sample using quota sampling and obtained sample of 70 workers from both divisions. This study was sourced from primary data using the Maslach-Trisni Burnout Inventory, work motivation, and social support questionnaire distributed via paper and google form. Data were analyzed using the chi-square test. The results showed 41.4% of workers experienced high burnout syndrome. There is relationship between gender (p-value=0.039) and work motivation (p-value=0.032) with burnout syndrome. It is expected that PT PLN (Persero) Head Office can increase appreciation to workers, cooperate with third parties, and conduct internal evaluations to prevent and reduce risk of burnout syndrome.